Diagnostic concordance of clinical diagnosis, tissue culture, and histopathology testing for skin and soft tissue infections: A single-center retrospective study - Christina M. Herbosa, BA; Trisha S. Bhat, BA; Yevgeniy R. Semenov, MD; Ilana S. Rosman, MD; Amy C. Musiek, MD (Wolters Kluwer, 2020)
Background: Tissue culture and histopathology are the conventional diagnostic modalities for skin and soft tissue infections (SSTIs), but few studies have investigated their concordance. Objective: Determine concordance between histopathology and tissue culture in the diagnosis of suspected SSTIs. Methods: Single-center retrospective study of 355 cases with suspected SSTIs identified from the dermatology inpatient consultation log January 2014-July 2017. Results: Overall concordance between histopathology testing and tissue culture results was high (76.1%). Concordance was high for cases defined as no evidence of infection, fungal infection and mycobacterial infection by histopathology (77.8%, 74.2%, and 80.0%) and tissue culture (92.1%, 67.7%, and 83.3%). Concordance was lower for suspected SSTIs with bacterial infection by histopathology (61.9%) and tissue culture (28.4%). Concordance rates were not significantly affected by age, sex, race, antimicrobial agent use, immunologic status, or biopsy size. Limitations: Retrospective and single-institution nature of the study. Conclusion: This study demonstrated a high concordance between histopathology and tissue culture in SSTIs with no clinical evidence of infection and suspected fungal and mycobacterial SSTIs, though concordance was lower for suspected SSTIs with evidence of bacterial infection. Clinicians should not be deterred from relying on initial histopathological results based on patients' immunosuppressed status, antimicrobial agent use, age, or biopsy tissue size.